2006
DOI: 10.1002/ange.200603013
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Waterwheel (Noria) from a Simple Condensation of Resorcinol and an Alkanedial

Abstract: Eine überraschende Ringbildung ist das Resultat der Reaktion von Resorcin mit 1,5‐Pentandial in Ethanol bei 80 °C in Gegenwart von konz. HCl. Das lösliche cyclische Oligomer, das binnen 48 h in hoher Ausbeute (83 %) unter thermodynamischer Kontrolle entsteht, hat laut Röntgenstrukturanalyse eine wasserradähnliche Struktur mit einem großen hydrophoben Hohlraum in der Mitte (siehe Bild). Ein Carbonsäureester‐Derivat erwies sich als hoch selektiv für Rb+‐Ionen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…It was discovered recently, that some of them are permanent porous with high surface areas of up to 1377 m 2 g À1 and selective gas-sorption properties. One example is the so-called Noria from Nishikubo et al, [19] which was reinvestigated by Atwood and coworkers. [20] Unlike the above-mentioned materials, this compound does have not to be crystalline to adsorb reasonable amounts of gases: The amorphous material has a BET surface area of 350 m 2 g…”
mentioning
confidence: 97%
“…It was discovered recently, that some of them are permanent porous with high surface areas of up to 1377 m 2 g À1 and selective gas-sorption properties. One example is the so-called Noria from Nishikubo et al, [19] which was reinvestigated by Atwood and coworkers. [20] Unlike the above-mentioned materials, this compound does have not to be crystalline to adsorb reasonable amounts of gases: The amorphous material has a BET surface area of 350 m 2 g…”
mentioning
confidence: 97%
“…In this context, only a few compounds have been studied to date. For example, Atwood and coworkers demonstrated that an organic cage compound called noria [16] adsorbs reasonable amounts of gases although it is in an amorphous state. The compound can selectively take up CO 2 (2.5 mmol g À1 at 30 bar and 298 K) in preference to N 2 despite the relatively small measured surface area of 350 m 2 g À1 (BET) and pore volume of 0.13 cm 3 g À1 .…”
mentioning
confidence: 98%
“…In dieser Hinsicht wurden bisher nur einige wenige Verbindungen studiert. Beispielsweise zeigten Atwood und Mitarbeiter, dass eine organische Käfigverbindung namens "Noria" [16] auch als amorphes Material beachtliche Gasmengen adsorbiert. Die gemessene BET-Oberfläche (350 m 2 g À1 ) und das gemessene Porenvolumen (0.13 cm 3 g À1 ) sind relativ klein, doch die Verbindung nimmt bevorzugt CO 2 statt N 2 auf (2.5 mmol g À1 bei 30 bar und 298 K).…”
unclassified